Makna Simbolik Tradisi Sambulu Gana dalam Pernikahan Suku Kaili Rai di Kelurahan Mamboro Barat, Kecamatan Palu Utara - Virgiawan, Eksal (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims, firstly, to describe how the process of the sambulu gana tradition in the marriage custom of the Kaili Rai Tribe in Mamboro Barat Village, North Palu District. The second is to describe what the symbolic meaning of the sambulu gana tradition is in the Kaili Rai Tribe Wedding in Mamboro Barat Village, North Palu District. This research is a qualitative research using snowball sampling method. The main purpose of using the descriptive method is to describe the nature of a situation that is currently running at the time the research is conducted and to examine the causes of a particular symptom. The informants in this study were the traditional leaders and traditional leaders of the Kaili Rai tribe in Labuan Beru. Data collection techniques were carried out through three steps, namely: (1) direct observation, (2) interviews, (3) documentation. The results of this study indicate that the people of West Mamboro Village, North Palu District, when married, must carry out the traditional sambulu gana tradition consisting of areca nut, betel nut, lime, tobacco, gambier, one goat and one gold ring. The sambulu gana custom is a custom that must be carried out in the marriage of the Kaili Rai tribe in the West Mamboro Village, North Palu District.